Collaboration In The Supply Chain of Road Safety System Division (RSSD) at Titan Indonesia to Improve Effectiveness and Efficiency Operational Performance - Rahmanda, Anggun; Simatupang, Togar M (The Indonesian Journal of Business Administration, 2012)
The purpose of this paper is to give the root cause and several strategies as a business solution to improve RSS division performance with creating a good business model and strategy of supply chain operation in terms of effectiveness and efficiency of business process division, to improve its operational performance in order to meet its customer needs and wants.Design/methodology/approach – By using The Porter’s 5 Forces analysis to examine the fundamental characteristics and structures. Five forces model of Porter is a framework for evaluating the industrial structure (business threats and opportunities) according to: the effects of rivalry, threat of entry, supplier’s power, buyer’s power, and threat of substitutes. The business issues exploration will be carried out by reviewing inbound supply chain, outbound supply chain, and business process. The root cause analysis of this case study was carried out to illustrate the applicabalityt of the framework.Findings –The findings show that adoption of collaboration in supply chain concept facilitates the chain members to have a broader view to develop and ensure an effective collaboration.Research limitations/implications –The analysis would only cover the time period of 2010 to 2012 as the past data because of the age of the existing division; The analysis only covers in-depth operational performance optimization strategy related to business channels performance that affects the RSSD profitability. Practical implications – The concept of Supply Chain Collaboration can be used by the chain members in the discussion forum to (re)design appropriate settings of the five elements of the architecture that lead to better overall performance.Keywords: Collaborative Supply Chain System, Information Sharing, Incentive Alignment, Decision Synchronization, and Innovative Suply Chain Processes.